‘This is not a drill’: Police and partnership preparedness for consequences of the climate crisis - Lydon, David (International journal of police science & management, 2025)
This scoping study investigates the state of preparedness of the police and their partners for the potential consequences of the climate crisis in a United Kingdom (UK) context. The research engaged participants at strategic, tactical and operational levels of planning and operations, and conducted a thematic analysis of qualitative data to identify key themes: climate change impacts; why the police should care; prioritisation and preparation; and enabling and impeding factors. The results suggest that the police and their partners may be ill-prepared for the gamut of possible consequences. Preparedness appears hampered by a narrow focus on legislated requirements, short-term planning, lack of funding and resources, and limited prescience. Recommendations are made for redefining planning parameters, strengthening central government engagement, amplifying awareness and understanding of trend analyses, prioritisation of ‘futures’ thinking, ethical considerations and collaborative preparedness. The study has implications for law, public policy and professional practice in the UK, and other global jurisdictions seeking to develop risk assessment processes and preparedness for the consequences of climate change.